Legal Issues in Limiting Authority of Health Professional Organizations After Indonesia’s 2023 Health Law Enactment - Rahman, Fauzi; Sapsudin, Asep; Margaretha (Research Horizon, 2025)
The enactment of Law Number 17 of 2023 on Health has raised significant concerns regarding its implications for the role and authority of health professional organizations in Indonesia. This new law is perceived as failing to uphold the functions previously guaranteed under earlier health-related regulations. This study aims to examine the legal challenges arising from the reduction of authority granted to Indonesian health professional organizations following the enactment of the Omnibus Health Law Number 17 of 2023, as well as its impact on their legal status and functional authority. Using a normative legal approach, this research applies statutory and conceptual methods, relying on both primary and secondary legal materials. The findings reveal that the diminished authority of health professional organizations has weakened their regulatory capacity, disrupted standard-setting mechanisms, and created institutional fragmentation. This condition hinders effective professional oversight and threatens public health protections. The legal restructuring introduced by the new Health Law undermines the coherent role of health professional organizations and necessitates future legal clarification or revision.